EVALUATION AND MANAGEMENT OF DIABETIC FOOT ACCORDING TO WAGNER’S CLASSIFICATION A STUDY OF 100 CASES - Muqim, Rooh -Ul-; Griffin, Samson; Ahmed, Mukhtar (Journal of Ayub Medical College Abbottabad, 2003)
Background: Wagner’s classification is the most widely utilized grading system for lesions of the diabetic foot. The aim of the study was to evaluate and manage the different lesions of diabetic foot according to Wagner classification. This will help to describe the lesions we treat study and compare outcomes and also identify measures to decrease morbidity and mortality due to diabetic foot disease. Methods: the study was conducted in surgical c unit of Khyber Teaching Hospital, Peshawar from July 2002 to June 2003. 100 patients with diabetic foot disease were included in the study. Detailed history, clinical findings and investigations were recorded. Lesions were graded according to wagner classification and appropriate medical and surgical treatment carried out. Results: diabetic foot disease formed 1.04% of total admissions and 0.23% of OPD patients. 62 (62%) were males and 38 were females. Common age group was 40 - 60 years, 6 patients had grade 0, 14 grade 1, 25 with grade 2, 30 with grade 4 and 4 with grade 5 lesions. 17 patients were managed conservatively with antibiotics alone, 33 had incision drainage and debridement while 48 needed amputation of different types. Staphylococcus aureus was the commonest organism isolated. Conclusion: majority of the diabetic foot lesions were in grade 2 to 5. Lesser grade lesions responded well to conservative treatment with antibiotics and surgical debridement while those with higher grades needed amputations. Effective glycemic control, timely hospital admissions, approximate surgical / medical treatment along with patient education in foot care can decrease morbidity and mortality due to diabetic foot disease. Key words: Diabetes mellitus, Complications, Diabetic foot disease, Wagner’s classification.